Penguatan Karakter Siswa Milenial Berbasis Islam di Madrasah Aliyah - Subki, Imam; Imami, Agus Sulthoni (Scaffolding: Jurnal Pendidikan Islam dan Multikulturalisme, 2022)
The purpose of this research is to determine the strengthening character of Millenial students based on Islam at MA Bustanul Faizin Besuki Situbondo. This study uses an intervention and habituation approach with data techniques from literature studies, field observations, documentation, and interviews. The subjects of this research are Madrasah Aliyah students at MA Bustanul Faizin while the object includes character education for students at MA Bustanul Faizin. The results of the study stated that the first, in terms of intervention, this school has reached a good level in the preparation of a curriculum that has been adjusted by the school environment, the situation of students and teachers and has covered all aspects of the existing subjects. Second, in terms of habituation, it has been said to be a very good level successful in strengthening positive characters for students at MA Made in Faizin with existing habits that contain good moral inculcation. In MA Bustanul Faizin's efforts to maintain and be sustainable, positive moral education and education are continuously carried out in spontaneous, scheduled, and habituation activities through national and religious events.